Genetic diversity and morpho-agronomic characterization of Gobhi sarson (Brassica napus L) genotypes - Aazima Hyder; Asif M Iqbal; FA Sheikh; FA Sheikh; Sanjay K; SS Mahdi; ZA Dar; NR Sofi; MA Aziz; Qazi Iram; F Jeelani; S Bangroo (Journal of Oilseed Brassica, 2026)
The present study was carried out to assess the genetic diversity and to characterize the set of fifty Gobhi Sarson(Brassica napus L) lines during Rabi 2019-2020. Extent of diversity was estimated and distinctness among the cultivatedvarieties was established. Divergence analysis categorised the genotypes in to 8 clusters using Mahalanobis D2 analysis.Cluster II contained the maximum no. of genotypes i.e. 18 genotypes followed by Cluster III (11 genotypes), Cluster I (9genotypes), Cluster IV (6 genotype), Cluster V (2 genotype), Cluster VI (2 genotype), Cluster VII (1 genotype) andCluster VIII (1 genotype). It was observed that seed yield contributed maximum (25.2%) towards divergence, followed bymain raceme length (21.9%), no. of seeds silique-1 (18.3%), no. of pods plant-1 (13.4%), 1000 seed weight (8.5%), oilcontent (5.5%), days to 50 per cent flowering (4.2%) and days to 80 per cent maturity (2.9%). Since the inter clusterdistance between Cluster I and V (154.9), followed by Cluster V and VIII (145.1), was found quite large. Also, all thegenotypes were characterized for 24 morphological traits as per DUS Descriptor of PPV&FRA, 2001. A good spectrum ofvariation was found in the frequency distribution of genotypes for various characters.